Application of Silver Diamine Fluoride in Dental Trauma: A Case Series Study - Mridula Goswami; Vashi Narula; Babita Jangra (Bulletin of Emergency and Trauma)
Objective: Dental injury is a significant issue in children due to their immature physical, cognitive, and physiological development. These factors often result in heightened fear and behavioral challenges during their first visit following trauma, which can compromise the quality of treatment and lead to a poor prognosis for the affected tooth. Silver Diamine Fluoride (SDF), a colorless solution approved by the US FDA for treating dental hypersensitivity and caries, offers a simple, painless, and non-invasive treatment option. Its application involves a paint-on technique with a powerful fluoride formulation, making it an ideal choice for the initial management of enamel and dentin fractures in primary teeth, particularly in uncooperative young children.Case Description: This case series described four cases in which SDF was successfully used as the primary treatment for Ellis Class IX anterior tooth trauma in very young children with negative behavior responses in the dental setting. The procedure required minimal armamentarium and was well-tolerated by all patients.Conclusion: In each case, the use of SDF yielded successful and satisfactory outcomes, with a favorable prognosis for the affected teeth. Additionally, the treatment contributed to a positive shift in the children’s attitudes toward dental care.